1975
DOI: 10.1136/pgmj.51.601.801
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of lead from dust and soil

Abstract: Summary The lead burdens for children and mothers exposed to lead-contaminated soils and dusts have been investigated in a rural district with minimal atmospheric pollution. A significant relationship was observed between the lead content of blood and hair of children exposed to soils of mean lead content in the range 420-13,969 p.p.m. The blood lead concentration of children was consistently greater than that of their mothers. No consistent relationship was found between blood lead values and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 6 publications
(7 reference statements)
3
16
0
1
Order By: Relevance
“…A comparison with Table 3 shows that mining area PbB concentrations are generally lower than in smelter areas, some of which have large percentages of subjects with PbB concentrations of more than 40 J-Lg dL -1 • Whilst PbB concentrations may be lower than in smelter areas, there is nevertheless a considerable risk of Pb exposure in mining areas. In a study in Derbyshire, the venous PbB concentrations of 82 children were associated with their rates of exposure to environmental Pb (Barltrop et al, 1975). Those living in houses with garden soil Pb concentrations of less than 1,000 j.Lg g-1 had the lowest mean PbB concentrations of 20.7 j.Lg dL -1 (n = 29): those exposed to higher concentrations (1,000-10,000 j.Lg g-1 and >10,000 j.Lg g-1) had correspondingly higher mean PbB concentrations of 23.8 j.Lg dL -1 (n = 43) and 29 j.Lg dL -1 (n = 10), respectively.…”
Section: Metal Concentrations In Residents Of Smelter Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison with Table 3 shows that mining area PbB concentrations are generally lower than in smelter areas, some of which have large percentages of subjects with PbB concentrations of more than 40 J-Lg dL -1 • Whilst PbB concentrations may be lower than in smelter areas, there is nevertheless a considerable risk of Pb exposure in mining areas. In a study in Derbyshire, the venous PbB concentrations of 82 children were associated with their rates of exposure to environmental Pb (Barltrop et al, 1975). Those living in houses with garden soil Pb concentrations of less than 1,000 j.Lg g-1 had the lowest mean PbB concentrations of 20.7 j.Lg dL -1 (n = 29): those exposed to higher concentrations (1,000-10,000 j.Lg g-1 and >10,000 j.Lg g-1) had correspondingly higher mean PbB concentrations of 23.8 j.Lg dL -1 (n = 43) and 29 j.Lg dL -1 (n = 10), respectively.…”
Section: Metal Concentrations In Residents Of Smelter Areasmentioning
confidence: 99%
“…Such differences depend on the source of the metal, the environmental conditions it is subjected to and the amount of time that has elapsed since the lead was exposed to the environment. Several authors have stated the importance of the chemical form of contaminant metals in assessing their bioavailability and toxicity (Barltrop et al, 1975;Biggins and Harrison, 1980;Khan and Frankland, 1983;Gibson and Farmer, 1984;Wixson and Davies, 1994).…”
Section: Chemical Form and Bioavailabilitymentioning
confidence: 99%
“…In one study, mothers occupying the same dwelling had much lower PbB levels than those observed in children (28). However, the PbB levels in mothers from highly contaminated areas appeared to be elevated above PbB levels of mothers from areas of minimal lead contamination.…”
Section: Studies In Adultsmentioning
confidence: 89%
“…Ως πηγή εισόδου του Pb στον οργανισμό των παιδιών, στην περιοχή αυτή, θεωρείται το αναπνευστικό σύστημα με την αναπνοή της μολυβδούχου σκόνης (Barltrop et al, 1975). Ανάλογη μελέτη που έγινε κοντά στο χωριό Shipham στο Somerset της Μεγάλης Βρετανίας περιοχή στην οποία γινόταν εκτεταμένη εξόρυξη σμισθονίτη μεταξύ 1700 και 1850 με ευρεία διασπορά Ζη και Cd έδειξε ότι: α) το Cd στο έδαφος των κήπων της περιοχής αυτής υπερέβαινε τα 60 ppm.. β) Η σκόνη των σπιτιών χαρακτηριζόταν από μέση συγκέντρωση Ζη 2.300 ppm και 26 ppm.…”
Section: ποιοτητα εααφων και υγεια του ανθρωπουunclassified